2016
DOI: 10.1021/acscatal.6b01464
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Hinders Deactivation of Copper-Mordenite: Dimethyl Ether Carbonylation

Abstract: A plethora of previously unimaginable low-temperature C 1 and C 2 valorization reactions have become possible after the discovery of metal-exchanged solid-acid catalysts, with the most promising candidate being copper-mordenite. We show the dramatic effect of zinc addition to copper-exchanged mordenite in maintaining high Cu dispersion and reducing the catalyst poisoning as it relates to carbonylation of dimethyl ether to methyl acetate. Zinc maintains 90%+ selectivity even during deactivation versus 60% for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 24 publications
(47 reference statements)
1
42
0
Order By: Relevance
“…Most often, only one metal was ion‐exchanged, such as copper, silver, iron, zinc or nickel, but some bimetallic combinations (such as Cu−Pt/MOR or Ag/Pt/MOR) were also shown to enhance the activity as compared to the monometallic counterparts. Earlier,, we found that a certain Cu−Zn bimetallic combination on MOR provides a significant enhancement in the lifetime (Figure ) and suppresses coke deposition, and we hypothesized that metals affect certain acid sites on a MOR.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Most often, only one metal was ion‐exchanged, such as copper, silver, iron, zinc or nickel, but some bimetallic combinations (such as Cu−Pt/MOR or Ag/Pt/MOR) were also shown to enhance the activity as compared to the monometallic counterparts. Earlier,, we found that a certain Cu−Zn bimetallic combination on MOR provides a significant enhancement in the lifetime (Figure ) and suppresses coke deposition, and we hypothesized that metals affect certain acid sites on a MOR.…”
Section: Introductionmentioning
confidence: 73%
“…The observed nanoparticles are mostly above 5 nm in size, implying that they are located on the external surface of the MOR crystal. Given that the Cu dispersion measured by CO adsorption in the fresh catalysts is 42 % for the Cu/MOR and 63 % for all bimetallic catalysts and that porosity measurements (Section 2.2) did not reveal significant pore blockage, most of the metals are present as ionic species and not as nanoparticles. The most efficient spent 1Cu‐4Zn/MOR catalyst does not show any nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be ascribed to the unique implanting‐type structure of CuZn@ m −Al 2 O 3 catalyst and the higher Al content (60 % vs. 10 %). Moreover, CuZn@ m −Al 2 O 3 catalyst shows lower methane content than CuZn/ m −Al 2 O 3 catalyst, originating from the suppressed formation of methane or the promoted conversion of the as‐formed methane to methanol by intensified Cu−ZnO interaction. For another, we compared the catalytic performance of the implanted single component catalysts (Cu@ m −Al 2 O 3 and Zn@ m −Al 2 O 3 ) to present a further insight.…”
Section: Methodsmentioning
confidence: 99%